'Ode to Paraphernalia': Bricolage as a design approach for electronic performance tools. Issue 1 (1st March 2013) - Mauro-Flude, Nancy
This critical analysis is to addresses the implications about emerging design approaches in Human Computing Interfaces (HCI), and Human Interface Devices (HID). A reflection about custom-built interfaces invigorates a wider discussion about the meaningful contexts in which their use is activated. The specific aim is to re-imagine, redefine and explore the potentiality and limitations of electronic performance tools, namely, how the choice of this tool and interface nearly always gives rise to new situations that must be tackled. Therefore, addressing the material aesthetics of performance tools used in contemporary electronic performance, by artists who engage with such technologies, this article aims to critically analyse and historically place artistic engagement with tools and interfaces in contemporary performance settings and to indicate where there is room for new design approaches and hence new (and forgotten) modes of engagement to unfold. To amplify the relationship between performer and the spectator when using the emerging technologies of real-time performance tools, I refer to 'Ode to Paraphernalia', a set of self-crafted electronic performance tools and a performance. This project opens a pathway for a larger proposal that asks: what are the ways in which we can engineer interfaces that validate the circulation of subjugated knowledges in meaningful sets and settings?